2019
DOI: 10.1021/acs.estlett.9b00412
|View full text |Cite
|
Sign up to set email alerts
|

Volatility and Viscosity Are Correlated in Terpene Secondary Organic Aerosol Formed in a Flow Reactor

Abstract: Secondary organic aerosol (SOA) is a complex mixture of largely unspeciated compounds. The volatility and viscosity of the bulk organic aerosol influence new particle formation, processing, and lifetime in the atmosphere. Relationships between these properties are well-defined for pure compounds but currently unavailable for bulk organic aerosol. In this survey study, we characterized SOA formed from a range of biogenic precursors and conditions in an oxidation flow reactor for volatility (thermodenuder), visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 87 publications
4
29
0
Order By: Relevance
“…Although this is not an issue here, there are only few studies that quantify equilibrium water content in that regime. For example, measurements of water uptake by secondary organic aerosol (Varutbangkul et al, 2006;Jurányi et al, 2009;Petters et al, 2009;Good et al, 2010;Massoli et al, 2010;Chu et al, 2014;Pajunoja et al, 2015) have focused on RH > 50 % and room temperature. The lack of appropriate water activity data remains an impediment to fully characterize the phase diagram for other organic aerosols, including limiting full confidence in predictions of the phase state in large-scale atmospheric models.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is not an issue here, there are only few studies that quantify equilibrium water content in that regime. For example, measurements of water uptake by secondary organic aerosol (Varutbangkul et al, 2006;Jurányi et al, 2009;Petters et al, 2009;Good et al, 2010;Massoli et al, 2010;Chu et al, 2014;Pajunoja et al, 2015) have focused on RH > 50 % and room temperature. The lack of appropriate water activity data remains an impediment to fully characterize the phase diagram for other organic aerosols, including limiting full confidence in predictions of the phase state in large-scale atmospheric models.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of molecular structure and functional groups on glass transition temperature (T g ), a parameter determining a phase transition between amorphous solid and semisolid states, are not considered in those studies. Recently, the close relation between volatility and viscosity have been proved (Zhang et al, 2019;Champion et al, 2019), and parameterizations are developed to predict viscosity based on O/C and volatility at 11 global sites (Li et al, 2020). However, the simulation of the phase state and viscosity of OA in NCP during wintertime have not yet been made, impeding our understanding of the phase states of OA and its potential impacts.…”
Section: ;mentioning
confidence: 99%
“…However, studies of SOA material generated from the oxidation of single biogenic VOCs, including isoprene and various terpenes, have shown that SOA becomes highly viscous semisolids or glassy solids under certain environmental conditions such as low temperature and low RH. 8,[26][27][28][29][30][31][32][33][34][35][36][37][38] Increases in viscosity lead to much slower diffusion rates within the SOA, impacting particle growth and evaporation, gas-particle partitioning, size distributions, multiphase chemistry, and the ability of SOA to serve as nuclei for liquid cloud droplets or ice particles. 35,[39][40][41][42][43][44][45][46][47][48][49][50][51] The viscosity of SOA material depends on the molecular weight and the degree of oxidation of its chemical constituents.…”
Section: Introductionmentioning
confidence: 99%